Reduced frequency of T helper 17 and T helper 1 cells and their association with critical coronavirus disease 2019. Issue 5 (31st March 2021) - Shahbazi, Mehdi; Jafari, Mohammad; Moulana, Zahra; Sepidarkish, Mahdi; Bagherzadeh, Mojgan; Rezanejad, Maryam; Mirzakhani, Mohammad; Javanian, Mostafa; bayani, Masomeh; Sadeghi‐Haddad‐Zavareh, Mahmoud; Mehdinezhad, Hamed; Ghadimi, Reza; et al.
Abstract: There is very little knowledge about the immune responses, particularly cellular immunity to coronavirus disease 2019 (COVID‐19). The main objective of this study was to evaluate the frequency of T helper (Th) cell subtypes, including Th1, Th17, and Treg cells, in moderate‐to‐severe and critical COVID‐19 patients compared to healthy controls. Twenty‐nine moderate‐to‐severe and 13 critical patients confirmed for COVID‐19, and 15 healthy subjects were included in this study. Interferon‐γ (IFN‐γ)‐producing Th1 and interleukin‐17A‐producing Th17 and Treg cells in peripheral blood were measured with flow cytometry. The frequency of Th1 and Th17 was significantly decreased in critical patients compared to healthy subjects (aMD: −2.76 and − 2.34) and moderate‐to‐severe patients (aMD: −1.89 and − 1.89), respectively (p < 0.05). Differences were not significant between moderate‐to‐severe patients and healthy subjects for both Th1 (p = 0.358) and Th17 (p = 0.535), respectively. In contrast, significant difference was not observed between study subjects regarding the frequency of Treg cells. Patients with critical COVID‐19 had a markedly lower Th1/Treg and Th17/Treg ratios compared with the controls and moderate‐to‐severe cases. Our study showed a dysregulated balance of Th1 and Th17 cells and its relation to the severity of COVID‐19.